Towards providing the best Sharī'ah governance practices for Waqf based institutions - Hassan, Rusni; Syed Jaafar Alhabshi, Syed Musa; Yusoff, Adnan (IIUM Press, International Islamic University Malaysia, 2017)
Waqf is the donation for the sake of Allah (s.w.t). Historically, it isproven that society can benefit from waqf assets. Waqf assets can beused for religious purposes like building mosques, public health,transportation and education and others. However, due to the limitedregulatory framework and control over waqf institutions, there aremany undesirable issues regarding the Waqf management authority.Most of the issues are due to inadequate management of waqf andtheir accountability towards the donors and beneficiaries. If theseissues continue, the waqf institutions will have a negative publicimage and undermine the objective of the waqf leading peoplehesitant to donate to waqf. Thus, this paper highlights the negativeissues in the waqf institutions and proposes the need for Shari’ahgovernance. This paper proposes that Sharī‘ah governance practicesfor waqf institutions should be based on trust, accountability, Godconsciousness, hisbah, and mutual consultation. It is believed thatthis paper will alert the respective authorities and waqf managementto issue a Sharī‘ah governance framework.